The effect of dietary vitamin E on the pleopodal egg number of Astacus leptodactylus (Eschscholtz, 1823) - Harlioglu, MM; Köprücü, K; Özdemir, Y (Springer, 2002)
The effect of vitamin E on the pleopodal egg number of Astacus leptodactylus (Eschscholtz, 1823) was studied. Crayfish were fed 2% of their total wet weight daily with vitamin E supplemented diets and a control for 70 days. The vitamin E content of the control diet, diet 1, diet 2 and diet 3 were 20 mg kg(-1), 40 mg kg(-1), 80 mg kg(-1) and 160 mg kg(-1) respectively on a dry weight basis. Vitamin E levels of the control and experimental diets were analysed by High Performance Liquid Chromatography. Results showed that diets containing supplemental vitamin E were associated with an increase in the number of pleopodal eggs. The best result was obtained with diet 2 containing 80 mg kg(-1) supplemental vitamin E.
Keywords: Astacus leptodactylus; pleopodal eggs; vitamin E